Analisis Persepsi Peternak Indonesia Menuju Usaha Peternakan Berkelanjutan melalui Korporatisasi Peternak - Eriana Kartadjumena; Aida Wijaya; Andina Nur Fathonah; Erly Sherlita; Apriwandi; Debbie Christine (Jurnal EMT KITA, 2022)
The commitment of the Government of Indonesia in developing the livestock sector that focuses on business management that is environmentally friendly, pays attention to social conditions and is carried out with good governance needs to be supported by all stakeholders. One of them is the readiness and understanding of farmers in Indonesia to develop sustainable businesses through the corporatization of farmers that focuses on environmental, social and governance activities. This study aims to determine the perception of Indonesian farmers in developing sustainable livestock business through breeder corporatization that focuses on environmental, social and governance activities. The study was conducted on 49 respondents from Indonesian farmers through distributing questionnaires in the form of statements of understanding on environmental, social and governance issues towards sustainable livestock business through livestock corporatization. The results of this study indicate that Indonesian farmers have relatively understood sustainable activities that focus on environmental, social and governance issues. In addition, farmers through cooperatives as a form of breeder corporatization are relatively ready to implement, anticipate impacts and understand the control of sustainable livestock activities. However, farmers' understanding is still limited regarding the extent to which cooperatives are obligated to implement sustainability activities. Therefore, intensive socialization is still needed to get support from all levels of society in implementing sustainability activities in Indonesia.